The prevalence, distribution, and functional importance of lower limb somatosensory impairments in chronic stroke survivors: a cross sectional observational study. Issue 20 (25th September 2019) - Gorst, Terry; Rogers, Alison; Morrison, Stewart C.; Cramp, Mary; Paton, Joanne; Freeman, Jenny; Marsden, Jon
Abstract: Purpose: To investigate the prevalence and distribution of lower limb somatosensory impairments in community dwelling chronic stroke survivors and examine the association between somatosensory impairments and walking, balance, and falls. Methods: Using a cross sectional observational design, measures of somatosensation (Erasmus MC modifications to the (revised) Nottingham Sensory Assessment), walking ability (10 m walk test, Walking Impact Scale, Timed "Get up and go"), balance (Functional Reach Test and Centre of Force velocity), and falls (reported incidence and Falls Efficacy Scale-International), were obtained. Results: Complete somatosensory data was obtained for 163 ambulatory chronic stroke survivors with a mean (SD) age 67(12) years and mean (SD) time since stroke 29 (46) months. Overall, 56% ( n = 92/163) were impaired in the most affected lower limb in one or more sensory modality; 18% ( n = 30/163) had impairment of exteroceptive sensation (light touch, pressure, and pin-prick), 55% ( n = 90/163) had impairment of sharp-blunt discrimination, and 19% ( n = 31/163) proprioceptive impairment. Distal regions of toes and foot were more frequently impaired than proximal regions (shin and thigh). Distal proprioception was significantly correlated with falls incidence ( r = 0.25; p < 0.01), and centre of force velocity ( r = 0.22, p < 0.01). The Walking Impact Scale was the only variable that significantly contributed to a predictive model of falls accounting for 15–20% of the variance. Conclusion: Lower limb somatosensory impairments are present in the majority of chronic stroke survivors and differ widely across modalities. Deficits of foot and ankle proprioception are most strongly associated with, but not predictive, of reported falls. The relative contribution of lower limb somatosensory impairments to mobility in chronic stroke survivors appears limited. Further investigation, particularly with regard to community mobility and falls, is warranted. Implications for Rehabilitation: Somatosensory impairments in the lower limb were present in approximately half of this cohort of chronic stroke survivors. Tactile discrimination is commonly impaired; clinicians should include an assessment of discriminative ability. Deficits of foot and ankle proprioception are most strongly associated with reported falls. Understanding post-stroke lower limb somatosensory impairments may help inform therapeutic strategies that aim to maximise long-term participation, minimise disability, and reduce falls.